A 10‐year retrospective review of management and outcomes of pseudoaneurysms at a tertiary referral centre. Issue 5 (7th September 2021) - Schlegel, Richard N; Clements, Warren; Koukounaras, Jim; Goh, Gerard S; Joseph, Tim; Phan, Tuan; Moriarty, Heather K
Abstract: Introduction: Pseudoaneurysms are uncommon but potentially life‐threatening. Treatment may involve a variety of interventions including observation, manual compression, ultrasound‐guided thrombin injection and a variety of endovascular and surgical techniques. Current treatments are largely based on observational data and there is no consensus on management. This study aimed to provide evidence for guiding clinical decisions regarding visceral artery pseudoaneurysm and peripheral artery pseudoaneurysm management. Methods: Retrospective single‐centre review of patients diagnosed with visceral and peripheral artery pseudoaneurysms at a tertiary hospital (2010–2020). Results: There were 285 patients included in this study. A total of 86 patients were diagnosed with a visceral artery pseudoaneurysm, and 49 of these (57%) were caused by trauma. A total of 199 patients were identified with a peripheral pseudoaneurysm; 76 of these (38%) were caused by trauma and 69 (35%) were due to access site complication during an endovascular procedure. Initial technical success was achieved in 266 patients (93.3%) with 19 requiring an additional treatment to achieve success. Conservative treatment (100% success), endovascular treatment (98.1%) and surgery (100%) were more successful than ultrasound‐guided compression (63.6%) and thrombin injection (83.8%). The median time from diagnosis to intervention was <9 h for visceral artery pseudoaneurysms and 24 h for peripheral artery pseudoaneurysms. There was no change in survival outcomes with respect to time from diagnosis and intervention. Conclusion: In this study, pseudoaneurysms were treated with a high degree of success by observation or by using an endovascular approach, and those requiring endovascular intervention did not need to be treated immediately in an emergent setting.